Effect of Eurycoma longifolia Stem Extract on Uric Acid Excretion in Hyperuricemia Mice - Bao, Ruixia; Liu, Mengyang; Wang, Dan; Wen, Shaoshi; Yu, Haiyang; Zhong, Yi; Li, Zheng; Zhang, Yi; Wang, Tao (Frontiers in Pharmacology, 2019)
Aim of the study: Eurycoma longifolia is a tropic medicinal plant belonging to Simaroubaceae distributed in South East Asia. The stems are traditionally used for the treatment of sexual insufficiency, fever, hypertension, malaria. Furthermore, it has antidiabetic, and anticancer activities. Recently, it has been reported to reduce uric acid, but the mechanism is unclear.The aim of this study is to explore the effect and mechanism of E. longifolia stem extract (EL) and its active compounds on uric acid excretion. Materials and methods: Potassium oxonate (PO) induced hyperuricemia rats and adenine-PO induced hyperuricemia mice model were used to evaluate the effects of EL. Ultra Performance Liquid Chromatography was used to determine the levels of plasma or serum uric acid and creatinine. Hematoxylin-eosin staining was applied to observe kidney pathological changes, Western blot was applied to detect proteins expression levels of uric acid transporters. Effects of constituents on urate uptake were tested in hURAT1-expressing HEK293T cells. Results: EL significantly reduced serum and plasma uric acid levels at dosages of 100, 200 and 400 mg/kg in hyperuricemia rats and mice, and increased the clearance rate of uric acid and creatinine, improved the renal pathological injury. The protein expression levels of urate reabsorption transporter 1 (URAT1) and glucose transporter 9 were down-regulated while Sodium-dependent phosphate transporter 1 and ATP-binding cassette transporter G2 were up-regulated in the kidney after EL treatment. The diterpenes isolated from EL showed inhibitory effects on urate uptake in hURAT1-expressing HEK293T cells, and the effect of eurycomanol was further confirmed in vivo. Conclusion: Our findings revealed that EL significantly reduced blood uric acid levels and prevented pathological changes of kidney in PO induced hyperuricemia animal model, improved renal urate transports. We partly clarified the mechanism was related to suppressing effect of URAT1 by diterpene in EL.